Assessing electrocatalyst hydrogen activity and CO tolerance: comparison of performance obtained using the high mass transport ‘floating electrode’ technique and in electrochemical hydrogen pumps - Jackson,C; Raymakers,LFJM; Mulder,MJJ; Kucernak,ARJ (Applied Catalysis B: Environmental, 2020)
Current ex-situ electrochemical characterisation techniques for measuring the hydrogen reaction are insufficient to effectively characterise catalytic behaviour under CO containing environments. We show the high mass transport, floating electrode technique offers a solution as it adequately describes hydrogen oxidation (HOR) and evolution over a wide potential range, as needed for various electrochemical systems. The peak HOR mass activities measured on the floating electrode were 68–93 A.mgmetal-1 - significantly higher than achieved in an experimental setup of an electrochemical hydrogen pump (EHP, 6–12 A.mgmetal−1). This implies that the EHPs operate with a significant mass transport limitation. Additionally, poison tolerances of catalysts using low concentrations of 20ppm CO produced transient responses over ca. 500s which correctly followed the CO tolerances determined from EHPs (PtRu/C>Pt/C>PtNi/C). A model of the kinetic transient responses on the floating electrode is provided which aids in describing the catalytic behaviour in poisoned environments.